Lista florística comentada de la Estación de Biología Tropical "Los Thxtlas", Veracruz, México - Ibarra-Manríquez, Guillermo (Universidad de Costa Rica, 1995)
The Estación de Biología Tropical "Los Tuxtlas", (México) an ecological reserve of about 640 ha with tropical rain forest, has a vascular flora of about 940 species, 543 genera, and 137 families. For each species, a short description, growth form, height, kind and position of leaves, flower color, fruit color and type, phenology, uses, common name, and revised specimens are provided. The most diverse families in the preserve are Orchidaceae (108 species), Polypodiaceae s. l. (62), Asteraceae (60), Fabaceae s. l. (58) and Rubiaceae (39). The numerically more important genera are Epidendrum ( 1 6), Ficus (15), Piper (13), Eupatorium (11), and Psychotria (11). Trees and herbs are the most frequent growth forms: 31.7% and 30.4% respectively. This paper ¡neludes part 1 of the listo